Balancing dipolar and exchange coupling in biradicals to maximize cross effect dynamic nuclear polarization. Issue 24 (9th June 2020) - Equbal, Asif; Tagami, Kan; Han, Songi
Abstract : Balancing dipolar and exchange coupling is essential for efficient Cross Effect DNP. This explains the complex performance of standard radicals (AMUPOL and HyTek) at high magnetic field and fast spinning. Abstract : Dynamic nuclear polarization (DNP) by the cross effect (CE) has become a game changer for solid-state nuclear magnetic resonance (NMR) spectroscopy. The efficiency of CE-DNP depends on the strength of the electron–electron coupling in biradical polarizing agents. Hence, the focus lately has been on designing biradicals with a large net exchange ( J ) and dipolar ( D ) coupling. In this study, we reveal that the crucial factor for CE-DNP is not the large sum, J + D, but rather the relative magnitude of J and D, expressed as the J / D ratio. We show that the mechanistic basis of this interference lies in the isotropic vs. the anisotropic nature of the J and D couplings, respectively. This interference can lead to a small (effective) electron–electron coupling for many orientations even when J + D is large, resulting in non-adiabatic rotor-events. We find that when 0 < | J / D | < 1 the CE-DNP efficiency is attenuated for the majority of orientations, with greater attenuation observed at higher magnetic fields and faster magic-angle spinning (MAS) frequency. The interference effect of J and D coupling introduced in this study can explain why many biradicals with high or comparable J + D still show significantly divergent DNP performances. We debut J / D as a consequential criteria for designing efficient biradicals to robustly perform across a large range of B 0 fields and MAS frequencies.